Minorities in the constitutionalism of African States - (:unkn) unknown (My University, 2014)
The protection of minorities doesn't have an adequate framework. The protection of rights of this category of persons in political societies of Africa in general and in those of cent'ral africa in particular suffers of many obstacles. In one hand we have the problem of the definition of minorities. On the second hand, we have the implications of some political interests which make the protection of theirs rights very difficult to achieve. African states in general don't seriously take in hand the problem of the rights of minorities. As far as it is a problem of democraty and integration of all citizens un public affairs, it is very necessary to adress this important question.
Keywords: African Research